Periodontal Disease and Late-Onset Aortic Prosthetic Vascular Graft Infection - Stephanie Thomas; Jonathan Ghosh; Johnathan Porter; Adele Cockcroft; Riina Rautemaa-Richardson (Case Reports in Vascular Medicine)
Prosthetic vascular graft infection (PVGI) is a rare but significant complication of arterial reconstructive surgery. Although the relative risk is low, the clinical consequences can be catastrophic. Microbiological data on causative bacteria are limited. We present four cases of late-onset PVGI. Using a culture-independent nucleic acid amplification method for analysis of intraoperative samples, the presence of bacteria highly suggestive of an oral source was reported. Examination by an oral health specialist confirmed the presence of chronic periodontal disease. We hypothesize that chronic oral infection may be a previously unreported risk factor for the development of late-onset PVGI.